Targeting the CCL2-CCR2 axis for atheroprotection - Georgakis, Marios K; Bernhagen, Jürgen; Heitman, Laura H; Weber, Christian; Dichgans, Martin (European heart journal, 2022)
Decades of research have established atherosclerosis as an inflammatory disease. Only recently though, clinical trials provided proof-of-concept evidence for the efficacy of anti-inflammatory strategies with respect to cardiovascular events, thus offering a new paradigm for lowering residual vascular risk. Efforts to target the inflammasome-interleukin-1β-interleukin-6 pathway have been highly successful, but inter-individual variations in drug response, a lack of reduction in all-cause mortality, and a higher rate of infections also highlight the need for a second generation of anti-inflammatory agents targeting atherosclerosis-specific immune mechanisms while minimizing systemic side effects. CC-motif chemokine ligand 2/monocyte-chemoattractant protein-1 (CCL2/MCP-1) orchestrates inflammatory monocyte trafficking between the bone marrow, circulation, and atherosclerotic plaques by binding to its cognate receptor CCR2. Adding to a strong body of data from experimental atherosclerosis models, a coherent series of recent large-scale genetic and observational epidemiological studies along with data from human atherosclerotic plaques highlight the relevance and therapeutic potential of the CCL2-CCR2 axis in human atherosclerosis. Here, we summarize experimental and human data pinpointing the CCL2-CCR2 pathway as an emerging drug target in cardiovascular disease. Furthermore, we contextualize previous efforts to interfere with this pathway, scrutinize approaches of ligand targeting vs. receptor targeting, and discuss possible pathway-intrinsic opportunities and challenges related to pharmacological targeting of the CCL2-CCR2 axis in human atherosclerotic disease.